2011
DOI: 10.1890/10-0137.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of the superpopulation approach to estimate breeding population size: an example in asynchronously breeding birds

Abstract: Abstract. Many populations of animals are fluid in both space and time, making estimation of numbers difficult. Much attention has been devoted to estimation of bias in detection of animals that are present at the time of survey. However, an equally important problem is estimation of population size when all animals are not present on all survey occasions. Here, we showcase use of the superpopulation approach to capture-recapture modeling for estimating populations where group membership is asynchronous, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Estimation can be problematic for highly mobile and migratory animals, as individuals often occupy habitats asynchronously. Evidence suggests that capture-recapture methods that account for the temporal variability of annual residency are robust approaches for estimating abundance (Williams et al 2011). Hence, one of the most commonly used models to estimate abundance at migratory destinations is the superpopulation POPAN model Schwarz 1996, 1999), a derivative of the Jolly-Seber model (Jolly 1965, Seber 1965.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation can be problematic for highly mobile and migratory animals, as individuals often occupy habitats asynchronously. Evidence suggests that capture-recapture methods that account for the temporal variability of annual residency are robust approaches for estimating abundance (Williams et al 2011). Hence, one of the most commonly used models to estimate abundance at migratory destinations is the superpopulation POPAN model Schwarz 1996, 1999), a derivative of the Jolly-Seber model (Jolly 1965, Seber 1965.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that the POPAN model recovered true population sizes well. The results of the simulation study help to identify conditions under which the superpopulation model performs best (i.e., narrow confidence intervals and high accuracy; also see Williams, Frederick andNichols, 2011). As expected, the superpopulation model performs best when both survival and capture probabilities are high.…”
Section: Discussionmentioning
confidence: 59%
“…A primary benefit to this technique is the rapidity at which we can interpret data from satellites like Landsat, completing a classification within 1 day, as opposed to previous manual classifications of aerial imagery that can take months to years to complete (Rutchey & Vilchek ; Rutchey et al ). This is particularly important because mapping efforts are useful not only for monitoring invasive spread, but they are extremely important as data that can be used to understand process and pattern changes that occur with invasion (Norton‐Griffiths ; Williams et al ; Lowry et al ). A long period of satellite record affords the opportunity to create a database with wide spatial and temporal coverage.…”
Section: Discussionmentioning
confidence: 99%